If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -262 = -6(1 + 7x) + -4 -262 = (1 * -6 + 7x * -6) + -4 -262 = (-6 + -42x) + -4 Reorder the terms: -262 = -6 + -4 + -42x Combine like terms: -6 + -4 = -10 -262 = -10 + -42x Solving -262 = -10 + -42x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '42x' to each side of the equation. -262 + 42x = -10 + -42x + 42x Combine like terms: -42x + 42x = 0 -262 + 42x = -10 + 0 -262 + 42x = -10 Add '262' to each side of the equation. -262 + 262 + 42x = -10 + 262 Combine like terms: -262 + 262 = 0 0 + 42x = -10 + 262 42x = -10 + 262 Combine like terms: -10 + 262 = 252 42x = 252 Divide each side by '42'. x = 6 Simplifying x = 6
| 2x-5*3x-50=180 | | 6m-1=40m^2 | | (4x+16)(3x-9)=12x-36x | | (2x-5)(3x-50)=180 | | 4t-t= | | y^2+4y-72=180 | | 50x+4=7x+35 | | 0=k-9 | | y-11=1 | | -108=-3+7(7b-8) | | 4+y=15 | | 12x-5-8x+5=x-8x+5 | | 4x+10+10=180 | | 8y-(-5y-15)=13 | | y-15=-10 | | x^2+11x=4x+49 | | y+7y=40 | | 8h+3=75 | | -5n(4-3n)=10(n-2) | | 2x+2(4x)+38=180 | | 7-2n=8n(4n) | | 0.875p=-3.75 | | 7y-3x+8=0 | | 0.06666666666666666666666666666667-0.1666666666666667v=0.5333333333333333 | | x^2+7x=26 | | 10m-20=80 | | 5n+10= | | 14-y=0 | | 4x-3x=-6+8 | | 1+y=16 | | 3h+2=5h-15 | | -7j+-4j= |